2012
DOI: 10.4162/nrp.2012.6.3.232
|View full text |Cite
|
Sign up to set email alerts
|

The effect of salt usage behavior on sodium intake and excretion among Korean women

Abstract: This study was done to explore the effect of Korean women's salt usage behavior on their sodium intake and excretion according to aging. Dietary sodium intake and salt usage behavior were analyzed to compare the difference between young and middle-aged women. One hundred fifty six young women and 77 middle-aged women without hypertension or any current medication were recruited. Body mass index, waist hip ratio, blood pressure were measured from each subject. Salt usage behaviors were surveyed with questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 11 publications
0
10
1
1
Order By: Relevance
“…However, the link between carbohydrate intake and hypertension or impaired fasting glucose was unclear [8,9,11,14,38]. Being hypertensive with high carbohydrate intake in our results may be associated with high sodium intake by fermented vegetable in Koreans' traditional carbohydrate-rich diet or kidney related mechanisms by insufficient vitamin A consumption, not with carbohydrate intakes themselves [39,40]. We did not find the association between carbohydrate intake and obesity, hypercholesterolemia or metabolic syndrome.…”
Section: Discussioncontrasting
confidence: 66%
“…However, the link between carbohydrate intake and hypertension or impaired fasting glucose was unclear [8,9,11,14,38]. Being hypertensive with high carbohydrate intake in our results may be associated with high sodium intake by fermented vegetable in Koreans' traditional carbohydrate-rich diet or kidney related mechanisms by insufficient vitamin A consumption, not with carbohydrate intakes themselves [39,40]. We did not find the association between carbohydrate intake and obesity, hypercholesterolemia or metabolic syndrome.…”
Section: Discussioncontrasting
confidence: 66%
“…Over 60% of salt intake in Tehran is the salt added in cooking or at the table [13]. Also, it is difficult to precisely measure salt intake [6, 47]. Therefore, in order to prevent the recall bias and since self-reported avoidance of salt intake has a high correlation with the actual behavior [48], the habit of adding salt in cooking and at the table was questioned.…”
Section: Methodsmentioning
confidence: 99%
“…To assess salt usage behaviours, we used a modified version of the salt usage behaviour questionnaire described by Kim et al . and Lee et al . We chose four items that showed positive correlations with the mean spot urine sodium in our pilot study, two items on salt intake habits and two items on high‐salt food consumption.…”
Section: Methodsmentioning
confidence: 99%
“…To assess salt usage behaviours, we used a modified version of the salt usage behaviour questionnaire described by Kim et al 19 and Lee et al 20 We chose four items that showed positive correlations with the mean spot urine sodium in our pilot study, two items on salt intake habits and two items on high-salt food consumption. Subjects scored the following statements on a 5-point Likert scale, with higher scores indicating higher salt consumption: (i) typical salt content of food eaten (very salty = 5, a little salty = 4, moderately salty = 3, little salty = 2, not salty = 1), (ii) frequency of adding salt or soy sauce to cooked dishes (always = 5, frequently = 4, usually = 3, seldom = 2, never = 1), (iii) frequency of eating kimchi or salted vegetables (more than 3 times a day = 5, 1-2 times a day = 4, 3-6 times a week = 3, 2-8 times a month = 2, less than once a month = 1) and (iv) frequency of eating soups or stews (more than 3 times a day = 5, 1-2 times a day = 4, 3-6 times a week = 3, 2-8 times a month = 2, less than once a month = 1).…”
Section: Methodsmentioning
confidence: 99%